2013
DOI: 10.1115/1.4024575
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cell Viability and Functionality in Vessel-like Bioprintable Cell-Laden Tubular Channels

Abstract: Organ printing is a novel concept recently introduced in developing artificial threedimensional organs to bridge the gap between transplantation needs and organ shortage. One of the major challenges is inclusion of blood-vessellike channels between layers to support cell viability, postprinting functionality in terms of nutrient transport, and waste removal. In this research, we developed a novel and effective method to print tubular channels encapsulating cells in alginate to mimic the natural vascular system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
147
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(154 citation statements)
references
References 37 publications
(40 reference statements)
2
147
0
Order By: Relevance
“…The design principle is the same as the microfiber hydrogels except for the lack of a core solution [29,30].…”
Section: Microfibersmentioning
confidence: 99%
“…The design principle is the same as the microfiber hydrogels except for the lack of a core solution [29,30].…”
Section: Microfibersmentioning
confidence: 99%
“…To enhance mechanical properties, they presented a fabrication process in which conduits were reinforced with carbon nanotubes (CNTs) [38]. They demonstrated that the bioprinting process could induce quantifiable cell death and that cells were able to recover and undergo differentiation with high-level cartilage-associated gene expression [39]. In another report, they designed a multi-arm bioprinter with two nozzles mounted on independent arms to concurrently print a filament structure and deposit cell spheroids between the filaments to create a hybrid structure to support the cell spheroids in three dimensions [40].…”
Section: Introductionmentioning
confidence: 99%
“…Current work in bioprinting using hyaluronan hydrogels and tubular channels encapsulating cells in alginate has accomplished the fabrication of biologically functional blood vessels [36]. Another group has implemented 3D bioprinting to fabricate living alginate/gelatin hydrogel valve conduits with anatomical architecture [37].…”
Section: Future Therapeutic Utility Of 3d Printed Cardiac Devicesmentioning
confidence: 99%